Critical inertia thresholds for frequency stability in renewable Energy-Integrated power systems - Abolfazl Hadavi; Mehrdad Tarafdar Hagh; Saeid Ghassem Zadeh (International Journal of Electrical Power & Energy Systems)
Recent developments in the electricity sector, coupled with the increasing adoption of Renewable Energy Sources (RESs), have led to a decline in the use of synchronous generators. Power grid systems are progressively optimizing the integration of RESs. As the proportion of renewable resource generators rises, the overall inertia of the power system diminishes, thereby affecting the stability of system frequency. This inertial reduction is characterized as either structural and permanent or as fluctuating on a daily and hourly basis, depending on the characteristics of the renewable resources involved. The present study addresses a significant research gap concerning the intricate relationship between the integration of renewable energy and system inertia, particularly in relation to frequency stability. While prior research has touched upon these themes, this study aims to provide a more comprehensive analysis. It examines the effects of varying levels of renewable energy penetration on the frequency stability of a simplified power system. By investigating the correlation between inertia and frequency stability, the study identifies the critical inertia threshold required to sustain system stability during significant disturbances. The results underscore the potential hazards associated with substantial reductions in inertia, which may heighten the risk of frequency instability and potential grid failure.